Selective Synthesis and Luminescence Properties of Nanocrystalline GdF3:Eu3+ with Hexagonal and Orthorhombic Structures. (27th December 2010) - Zhang, Xiaoting; Hayakawa, Tomokatsu; Nogami, Masayuki; Ishikawa, Yukari
Abstract : GdF3 :Eu 3+ nanophosphors with hexagonal or orthorhombic structure have been succeeded to be selectively synthesized at room temperature for the first time via a simple soft chemical route. The structure and morphology of GdF3 :Eu 3+ nanophosphors were controlled by using different fluoride precursors. Hexagonal GdF3 :Eu 3+ nanocrystals were formed when NaBF4 was used as a fluoride precursor, while orthorhombic GdF3 :Eu 3+ nanocrystals were obtained with NaF or NH4 F fluoride precursor. It was also experimentally revealed that hexagonal GdF3 :Eu 3+ nanophosphors emitted essentially stronger Eu 3+ luminescence than orthorhombic ones did. The formation mechanism of GdF3 nanocrystals and the possible reasons of the strong PL in hexagonal were discussed.